The nature of the Pleistocene-Holocene palaeosols in the Gaza Strip, Palestine - Ubeid, Khalid (Geologos, 2011)
The Pleistocene to Holocene succession in the Gaza Strip, Palestine, consists of an alternation of calcareous sandstones and reddish fine-grained deposits (palaeosols). The palaeosols can be subdivided into two main groups based on the sand-sized versus clay- to silt-sized grains: (1) the sandy hamra palaeosols, and (2) the loess and loess-derived palaeosols. The hamra palaeosols can, in turn, also be subdivided into two main types according to their colour and grain size: (1) light brown loamy to sandy hamra palaeosols, and (2) dark brown sandy clay hamra palaeosols. The hamra palaeosols are polygenetic and originated in humid environments. Their red colour results from ferric oxides coating the sand grains, but also by illuviation. The various pedogenitic units and their gradual transition to loess palaeosols are due to different phases of dust accretion. Both groups of palaeosols developed during the last glacial. They are considered to represent different climate environments: hamra palaeosols represent humid climates, whereas the loess and loess-derived palaeosols represent dry and semi-dry climates.